“Convenience” Orthodontics: Innovative integration of treatment mechanics – A case report - Handa, Ashish; Paul, Budhaditya (Journal of Case Reports in Dental Medicine, 2025)
Background: Space closure is one of the most perplexing progressions in the field of Orthodontics and involves a concrete understanding of biomechanics to evade any adverse side effects. The significance of time frame for orthodontic treatment is noticeable in the literature as numerous modalities of space closure have been proposed by the experts. Itâ€™s a known fact that the appropriate usage of Begg brackets makes orthodontic therapy more proficient and versatile; while raising the comfort level of the patient. A 21â€‘yearâ€‘old male patient visited our dental center with a chief concern about forwardly placed and spaced upper front teeth.Â Objective: This treatment modality had the objective to carry out orthodontic space closure with appropriate anchorage preservation bypassing initial leveling and alignment using Begg brackets in the minimal possible time.Methodology: Simultaneous intrusion and retraction were planned by bonding Begg brackets on the palatal surface of upper anteriors and pink elastics (3/8â€) were engaged from the transpalatal arch to these brackets to produce light forces of approx. 45-50 gms. These elastics were changed every 7-10 days.Results: After 07 months of this therapy, a significant amount of intrusion and retraction and complete closure of generalized upper anterior spacing was achieved. Cephalometric superimposition indicated intrusion and retraction of the maxillary anterior teeth primarily by translation.Conclusion: This mechanotherapy can be considered a viable and efficient treatment alternative as it carries significant advantages like enhanced patient satisfaction and compliance, maintained pre-treatment functional occlusion, simplified mechanics, reduced treatment duration, cost and patient burn-out.